Pengaruh Kualitas Layanan Dan Harga Terhadap Kepuasan Pengguna Jaringan Speedy Telkom Di Kota Nganjuk - Rendi Setiawan; Suparni Suparni (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2022)
Consumer behavior is closely related to the purchase decision. Quality of service is something that is able to fulfill the desire or needs of the customer to know the wants and needs of the consumer. Price has two main role in buyer decision process, that is role of allocation and information information. The purpose of this research is to prove and explain the influence of service quality and price simultaneously to user satisfaction using Telkom speedy service in Nganjuk area. The type of research used in this research is asosoatif research with quantitative approach. Type and source of research data in the form of primary and secondary data. Data collection techniques are questionnaires distributed to 75 respondents including households, teachers, cafes, private (agency office) using Slovin formula. Data analysis technique using multiple linear rgrensi analysis using statistic t test to test partially and F significance test for simultaneous washing The results of this study prove that (1) service quality partially influence on consumer decisions using Telkom services speedy. This means that the first hypothesis is acceptable and verifiable (2) the price has a partial effect on the consumer's decision to use telkom speedy service in the Nganjuk area. Means that the second hypothesis can be accepted and can be proven kebenaranya (3) User satisfaction simultaneously affect the consumer decisions using Telkom speedy service in the area nganjuk. This means that the third hypothesis is acceptable and can be proven to be true.